FORMING STUDENTS 'SKILLS OF PEACE, UNITY, JUSTICE AND PHYSICAL PERFECTION THROUGH THE FRIEND "ALPOMISH" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the formation of physical, spiritual and moral qualities in students through the epic "Alpomish".